2021
DOI: 10.1371/journal.pone.0250359
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking status and programmed death-ligand 1 expression on the microenvironment and malignant transformation of oral leukoplakia: A retrospective cohort study

Abstract: Tobacco smoking is associated with an increased risk of oral leukoplakia and head and neck cancer. Although it has recently been reported that the establishment of an immunosuppressive microenvironment in oral potentially malignant disorders may lead to malignant transformation, it is unclear whether the microenvironments of oral potentially malignant disorders differ according to smoking status. We examined differences in programmed death-ligand 1 (PD-L1) expression and subepithelial CD163+ TAM and CD8+ cell/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…reported a series including n = 200 OPMD in which the subepithelial CD163+ cell count was not associated with malignant transformation of OPMD. 36 …”
Section: Discussionmentioning
confidence: 99%
“…reported a series including n = 200 OPMD in which the subepithelial CD163+ cell count was not associated with malignant transformation of OPMD. 36 …”
Section: Discussionmentioning
confidence: 99%
“…FED has been morphologically defined as dysplastic foci related to HT [10,11]. Recently, several studies on PD-L1 expression in various dysplastic tissues have emerged: such as oral mucosa [36,37], respiratory epithelium [38], Barrett's esophagus [39], and anal epithelium [40]. PD-L1 expression both in dysplastic epithelium and accompanying lymphocytes has been higher in high-grade lesions (12% and 25% positivity) in comparison with low-grade dysplastic anal lesions (6% and 6% positivity) [40].…”
Section: Discussionmentioning
confidence: 99%
“…Chemicals in tobacco smoke cause chronic inflammation in the oral mucosa, which contributes to an immunosuppressive microenvironment. The results of Yagyuu et al suggested that non-smoking patients are less likely to develop OL than smoking patients [77]. However, once OL occurs in nonsmoking patients, it is associated with a higher risk of malignant transformation.…”
Section: Discussionmentioning
confidence: 99%